Children's Legal Status in Kediri Religious Court Marriage Dispensation Cases - Rachmatulloh, Mochammad Agus; Hikmiyah, Lailiyatul (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Marriage is permitted for those who have fulfilled the marriage requirements as regulated in statutory regulations. Among them, the minimum age for marriage for prospective male and female brides is the same, 19 years. For those who do not meet the minimum age requirements, marriage can still take place after receiving a marriage dispensation from the court. Data shows that there are a lot of requests for marriage dispensation in Indonesia, in fact every year there is a significant increase. The Kediri City Religious Court only has 3 sub-districts, in 2022, 69 marriage dispensation cases will be accepted. The reason that is often given is that the relationship between the prospective bridegroom and the female is very close, parents/guardians are afraid and worried that they will increasingly fall into actions that are contrary to morals or religion, and quite a few of the prospective wives are already pregnant. In adjudicating cases regarding requests for marriage dispensation, the court often considers two disadvantages, which occur as a result of early marriage and if the marriage dispensation is rejected. Interesting, knowing the practice and position of children in conflict with the law in cases of requests for marriage dispensation at the Kediri City Religious Court. The practice of marriage dispensation application cases is in accordance with general civil procedural law and statutory regulations, especially Law Number 16 of 2019, Law Number 23 of 2002, and Supreme Court Regulation Number 5 of 2019. The examination is in accordance with the principles -the principle of children dealing with the law, because every case involving children is required to consider the best interests of the child so that the determination must take an approach to the best interests of the child, which is carried out comprehensively.